2015
DOI: 10.1186/s13256-015-0527-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of a massive bilateral pulmonary embolus due to an entrapped thrombus in a patent foramen ovale: a case report

Abstract: IntroductionEntrapped thrombus in a patent foramen ovale is a rare form of right heart thromboembolism. Various treatments have been used, such as anti-coagulation and thrombolytic therapy, vena cava filter, percutaneous thrombectomy and surgical embolectomy.Case presentationA 60-year-old Kosovan woman was admitted to our hospital with a massive bilateral pulmonary thromboembolism, entrapped thrombus in the patent foramen ovale and severe right ventricular dysfunction. The patient underwent on-pump beating-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
1
0
2
Order By: Relevance
“…Several studies reported that almost 65% of such patients underwent surgery, and the mortality rate was 9.7% vs 36% and 32% mortality in patients who underwent thrombolysis or anticoagulation therapy. [7,8] In addition, the VA-ECMO device was used in our case to support the right ventricle and improve oxygen saturation. There are two types of ECMO: VA-ECMO and veno-venous (VV) ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that almost 65% of such patients underwent surgery, and the mortality rate was 9.7% vs 36% and 32% mortality in patients who underwent thrombolysis or anticoagulation therapy. [7,8] In addition, the VA-ECMO device was used in our case to support the right ventricle and improve oxygen saturation. There are two types of ECMO: VA-ECMO and veno-venous (VV) ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Cerrahi hem trombüsün temizlenmesi, hem de PFO' nun kapatılmasını mümkün kılar. Bu üç tedavi için mortalite oranları sırasıyla %9,7; %32 ve %36' dır (7). Medikal tedavi ile mortalitenin yüksek olmasının sebepleri, bu tedaviye yönlendirilen hastaların genel durumlarının daha bozuk olması, trombüsün fragmante olup yeni embolilere neden olması ve teşhisten tedaviye kadar geçen zaman uzadıkça antikoagülan ilaçların etkisinin azalması olabilir.…”
Section: Discussionunclassified
“…Medikal tedavi ile mortalitenin yüksek olmasının sebepleri, bu tedaviye yönlendirilen hastaların genel durumlarının daha bozuk olması, trombüsün fragmante olup yeni embolilere neden olması ve teşhisten tedaviye kadar geçen zaman uzadıkça antikoagülan ilaçların etkisinin azalması olabilir. Günlük pratikte bu tür olguların %65 oranında cerrahi tedavi aldığı görülmektedir (7). Baydoun ve ark.…”
Section: Discussionunclassified